(untitled) (KYAMC Journal, 2013)
A peptic ulcer, also known as peptic ulcer disease (PUD) is the most common ulcer of an area of the gastrointestinal tract that is usually acidic and thus extremely painful. It is defined as mucosal erosions equal to or greater than 0.5 cm. As many as 70%-90% of such ulcers are associated with Helicobacter pylori, a spiral-shaped bacterium that lives in the acidic environment of the stomach. KYAMC Journal Vol. 3, No.-2, January 2013, Page 270-272 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15164